Cloud Computing in Indonesia - Siddiq, Rasyid Fajar; Hasbullah M. Jufry; Dzikri Daud Alfatih; Faiz Daffa Makarim (Indonesian Journal of Electrical Engineering and Electronics, 2024)
In recent years, the amount of data generated in the world has increased rapidly. This data includes everything such as customer information, transactional data, sensor data, and digital media. With this ever-increasing amount of data, efficient and scalable data storage, processing, analysis is critical. Therefore, cloud computing is here as a solution to this problem. Cloud computing can provide efficient and flexible infrastructure and services. This research was conducted to elaborate the implementation of cloud computing technology in Indonesia. The research method used in this research is a qualitative descriptive method in which we describe cloud computing and its implementation in Indonesia. The implementation of cloud computing in Indonesia is still lagging behind compared to developed countries, this is due to a lack of marketing and uneven internet infrastructure. Even so, the implementation of cloud computing in the business, health, education and government sectors has been done quite well.